(untitled) - Box, George E. P. (Hoboken, N.J., 2007)
This is an ideal reference for researchers as well as a primary text for Response Surface Methodology graduate-level courses and a supplementary text for Design of Experiments courses at the upper-undergraduate and beginning-graduate levels
Keywords: Experimental design,Response surfaces (Statistics),Mixture distributions (Probability theory),Ridge regression (Statistics),Thiết kế thử nghiệm,Toán thống kê